Impact of the Youth Health Offices of the Portuguese IPDJ Cuida-Te Program on the Quality of Life, Well-Being, and Mental Health of Adolescents and Emerging Adults: A Pre-Post Analysis over 3 Years - Margarida Gaspar de Matos; Marta Raimundo; Ana Beito; Cátia Branquinho; Gina Tomé; Marta Reis; Tânia Gaspar (Adolescents, 2026)
The mental health of young people has increasingly emerged as a public health priority due to the growing prevalence of mental health problems during adolescence and early adulthood. The literature has identified community-based programs as effective strategies for promoting well-being and preventing psychological symptomatology. In this context, the present study aimed to evaluate the impact of the interventions provided by junior psychologists working in the Youth Health Offices of the Cuida-te Program of the Portuguese Institute of Sports and Youth (IPDJ) on the quality of life, well-being, and mental health of Portuguese youth through a pre- and post-intervention analysis. A total of 1164 young people, aged between 12 and 29 years old, participated across three editions of the program. Self-report instruments were used to assess the quality of life, the well-being, and the psychological symptoms (stress, depression, and anxiety) of the participants. The results revealed statistically significant improvements between pre- and post-intervention assessments, including increased quality of life and well-being, as well as reduced levels of stress, depression, and anxiety. These findings were observed among both female and male participants and across different age groups. Non-binary participants showed less pronounced results, although with no statistically significant differences identified, suggesting the need for more research with larger samples and for inclusive interventions tailored to the specific needs of sexual and gender minorities. Overall, the work carried out appears to constitute an effective and cost-effective community-based response for the prevention of mental health symptoms and the promotion of mental health in adolescents and young adults, reinforcing the importance of permanent, accessible, and inclusive public policies.